Mirror mechanism and dedicated circuits are the scaffold for mirroring processes. (29th April 2014) - Fogassi, Leonardo
Abstract: In the past decade many studies have demonstrated the existence of a mirror mechanism that matches the sensory representation of a biological stimulus with its somatomotor and visceromotor representation. This mechanism, likely phylogenetically very old, explains several types of mirroring behaviours, at different levels of complexity. The presence in primates of dedicated neuroanatomical pathways for specific sensorimotor integrations processes implies, at least in the primate lineage, a hard-wired mirror mechanism for social cognitive functions.